Pengaruh Profitabilitas, Likuiditas, dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Pilka Nursari; Menik Indrati (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2024)
The purpose of this study is to analyze the effect of Profitability, Liquidity, and Firm Size on Firm Value. This study consists of three independent variables consisting of Profitability proxied by Return On Equity (ROE), Liquidity proxied by Curren Ratio, and Company Size as proxied by Size, and one dependent variable, namely Firm Value proxied by PBV. In this study, there were 30 companies that met the criteria from a total observation of 45 companies with the object of research being LQ45 companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2021 period. This research uses Statistical Product and Service Solutions (SPSS). The results of this study indicate that the Profitability Variable has a positive effect on Firm Value. Liquidity variable has a positive effect on firm value. Firm size variable has a positive effect on firm value. For companies, it is expected to further improve the company's performance and pay attention to the variables of profitability, liquidity and company size which are considered important in the company that can affect stock prices and increase company value. With company size and high profitability followed by good financial management will increase the value of the company. For investors, it is advisable to be more careful in choosing companies, to invest their capital by looking at the profitability and liquidity of the company with the aim of increasing the expected stock return.